Responses of Cereal Aphids and Their Parasitic Wasps to Landscape Complexity. Issue 2 (13th September 2014) - Zhao, Zi-Hua; Hui, Cang; Hardev, Sandhu; Ouyang, Fang; Dong, Zhaoke; Ge, Feng
Abstract : The intensification of agriculture has caused a decline in the complexity of agricultural landscapes because of the expansion of arable lands and the removal of natural habitats. These landscape changes, which have substantial effects on natural enemies (e.g., parasitoids) and on biological control services, have received considerable attention recently. In the current study, we analyzed the effects of landscape complexity on cereal aphids and their parasitic wasps in 24 sites during a period of 3 yr. In total, 11 primary parasitoid species and 6 hyperparasitoid species, comprising 5, 220 individuals, were collected in our experiments. With the exception of two primary parasitic wasps ( Trioxys asiaticus Telenga and Toxares sp.) and one hyperparasitic wasp ( Dendrocerus carpenteri [Curtis]), most species were sensitive to landscape complexity after ≥1 yr. Species diversity, primary parasitism, and hyperparasitism increased with increasing landscape complexity. However, the relationship between the population density of active primary parasitoids (effective primary parasitoids) and landscape complexity was indicated by a quadratic function, not a linear function. The effective population density of primary parasitoids was maximal (2.04 individuals per 100 wheat stems) if the percentage of noncrop habitat was 38%. The hypothesis that landscape complexity may enhance the activity or higher diversity of primary parasitoids and hyperparasitoids was well-supported by our study. However, the hyperparasitoids had a more sensitive response to landscape complexity than the primary parasitoids. Further studies should aim to enhance the biological pest control of primary parasitoids and suppress hyperparasitoids by habitat manipulation. This technique could be used effectively for pest management in mosaic landscapes through habitat rearrangement and reorganization.